Hubungan Tingkat Kecemasan Menghadapi Ujian dengan Skor Mini Objective Structured Clinical Examination (OSCE) di FK UNDANA Tahun 2020 - Purba, Julya Dasura; Setianingrum, Elisabeth Levina Sari; Ratu, Kristian; Rante, Su Djie To Rante (Universitas Nusa Cendana, 2022)
Background : Medical students face many exams that trigger various levels of anxiety such as the Mini Objective Structured Clinical Examination (OSCE). Mini Objective Structured Clinical Examination (OSCE) is one of the causes of high anxiety among medical students. If this is not handled properly, it can have an impact on passing the Mini Objective Structured Clinical Examination (OSCE) for medical students. Aims : Knowing the relationship between the level of anxiety in facing exams with the passing of the Mini Objective Structured Clinical Examination (OSCE) in the students of the Faculty of Medicine, and knowing the characteristics of age, place of residence, and gender of Undana Faculty of Medicine students third, fifth, and seventh semester Methods : An observational analytic study with cross sectional design which was conducted on pre-clinical students of the Faculty of Medicine, University of Nusa Cendana, batch 2017, 2018, and 2020. The sampling technique was stratified random sampling with a total sample of 107 people. Anxiety level data was obtained from filling out the Hamilton Anxiety Rating Scales (HARS) questionnaire and the Mini OSCE value was obtained from data taken from the Medical Education Unit (MEU) of the Faculty of Medicine, Nusa Cendana University. Data analysis used Gamma and Somers'd test. Results : Samples had different levels of anxiety, including 11 people (10.28%) not anxious, 27 (25.23%) mild anxiety, 61 (57.01%) moderate anxiety. weight anxiety eight people (7.48%). The Mini OSCE graduation reported that the sample who passed was 86 people (80.37%) and did not pass 21 people (19.63%). Conclusion : There is a relationship between the level of anxiety facing the exam with the score of Mini Objective Structured Clinical (OSCE) in Medicine Of Undana on 2020